Respuesta :

Answer:

x = -2

Step-by-step explanation:

First, you need to subtract 2x from both sides. This is because you can't have the same variable (in this case, is x) on 2 different sides, you need to combine them. In this case, you're subtracting since positive (+) 2 and negative (-) 2 will cancel each other out.

3x + 6 = 2x + 4

-2x        -2x

_____________

This makes the equation:

x + 6 = 4

Now, all you need to do is subtract 6 from both sides. You're subtracting instead of adding to both sides, because positive (+) 6 and negative (-) 6 cancel each other out.

x + 6 = 4

    -6   -6

________

This makes the answer:

x = -2